Transcriptome analysis of thymic tissues from Chinese Partridge Shank chickens with or without Newcastle disease virus LaSota vaccine injection via high-throughput RNA sequencing. Issue 4 (1st April 2022) - Nie, Furong; Zhang, Jingfeng; Li, Mengyun; Chang, Xuanniu; Duan, Haitao; Li, Haoyan; Zhou, Jia; Ji, Yudan; Guo, Liangxing
ABSTRACT: The LaSota strain of Newcastle disease virus (NDV) is a commonly used vaccine to control Newcastle disease. However, improper immunization is a common reason for vaccine failure. Hence, it is imperative to thoroughly explore innate immunity-related molecular regulatory responses to the LaSota vaccine. In this text, 140 long non-coding RNAs (lncRNAs), 8 microRNAs (miRNAs), and 1514 mRNAs were identified to be differentially expressed by RNA sequencing analysis in the thymic tissues of Chinese Partridge Shank chickens after LaSota vaccine inoculation. Moreover, 70 dysregulated genes related to innate immunity were identified based on GO, Reactome pathway, and InnateDB annotations and differential expression analysis. Additionally, dysregulated lncRNAs and innate immunity-related mRNAs that could interact with dysregulated miRNAs were identified based on bioinformatics prediction analysis via the miRanda software and differential expression analysis. Among these transcripts, expression patterns of five lncRNAs, seven miRNAs, and six mRNAs were further examined by RT-qPCR assay. Both RNA-seq and RT-qPCR outcomes showed that 10 transcripts (MSTRG.22689.1, ENSGALT00000065826, ENSGALT00000059336, ENSGALT00000060887, gga-miR-6575-5p, gga-miR-6631-5p, gga-miR-1727, paraoxonase 2 (PON2), mitogen-activated protein kinase 10, and cystic fibrosis transmembrane conductance regulator (CFTR) were highly expressed, and 4 transcripts (MSTRG.188121.10, gga-miR-6655-5p, gga-miR-6548-3p, and matrix metallopeptidase 9 (MMP9) were low expressed after NDV infection. Additionally, two potential competing endogenous RNA networks (ENSGALT00000060887/gga-miR-6575-5p/PON2 or MSTRG.188121.10/gga-miR-6631-5p/MMP9) and some co-expression axes (ENSGALT00000065826/gga-miR-6631-5p, MSTRG.188121.10/gga-miR-6575-5p, MSTRG.188121.10/CFTR, ENSGALT00000060887/MMP9) were identified based on RT-qPCR and co-expression analyses. In conclusion, we identified multiple dysregulated lncRNAs, miRNAs, and mRNAs after LaSota infection and some potential regulatory networks for these dysregulated transcripts.